THE INFLUENCE OF LEADERSHIP, ORGANIZATIONAL CULTURE, WORK ENVIRONMENT AND COMMITMENT ON THE PERFORMANCE OF GOODS/SERVICES PROCUREMENT MANAGERS THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE IN THE RIAU ISLANDS PROVINCE - Azwandi; Muammar Khadafi; Chablullah Wibisono; Damsar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to analyze the influence of leadership, organizational culture, work environment, and competence on the performance of managers of procurement of goods/services with job satisfaction as an intervening variable in the Ministry of Health. The data used in this study is primary data obtained from distributing questionnaires to 145 employees managing the procurement of goods/services of the Ministry of Health as respondents. The sampling technique used is simple random sampling. Structural Equation Modeling (SEM) with AMOS was used to test the research hypothesis. The results of the direct influence analysis showed that leadership, work environment and competence had a positive and significant effect on job satisfaction, while organizational culture had a negative and insignificant effect on job satisfaction. Leadership, organizational culture and work environment have a positive and insignificant effect on performance, while competence and job satisfaction have a positive and significant effect on performance. The results of the indirect influence analysis show that leadership, organizational culture, work environment and competence have a positive and significant effect on performance through job satisfaction.